Orientasi Kajian Hadis Kontemporer Indonesia (Studi Artikel E-Jurnal Dalam Portal Moraref 2015-2017) - Nailil Huda; Ade Pahrudin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2018)
This study examines the development, orientation and characteristics of the study of contemporary traditions in all online journals PTKI Indonesia on the portal Moraref. According to R. Michel Feener and Daniel Djuned, the study of hadith in Indonesia is growing dynamically and PTKI is at the center of its development. This is contradictory to Martin Van Bruinessen and Ahmad Rafiqi's assertion that the opposite is even less likely to develop. The methodology used by the author is descriptive-content analysis. Where the authors make all the journal articles containing the hadith studies in the Moraref Portal as the main data in the study, in addition to the literature relating to the study of hadith as secondary data. This research found Characteristics of study of Hadith in Indonesia if traced through e- journals that have been indexed Moraref categorized in six categories, namely thematic Hadith Studies with the number of articles 80 articles, Hadith scholarship as many as 74 articles, Studies of Hadits and hadith thinking with 49 articles, as many as 35 articles Hadith Studies orientalisme as many as 36 articles Studies of living hadith as many as 18 articles. So the most dominant in the study of hadith in Indonesia is a thematic research both in religious rituals and social issues.